Congenital diaphragmatic hernia in Coffin Siris syndrome: Further evidence from two cases. Issue 2 (23rd November 2022) - Rimoldi, Martina; Rinaldi, Berardo; Villa, Roberta; Cerasani, Jacopo; Beltrami, Benedetta; Iascone, Maria; Silipigni, Rosamaria; Boito, Simona; Gangi, Silvana; Colombo, Lorenzo; Porro, Matteo; Cesaretti, Claudia; et al.
Abstract: Coffin‐Siris Syndrome (CSS) is a rare multi‐system dominant condition with a variable clinical presentation mainly characterized by hypoplasia/aplasia of the nail and/or distal phalanx of the fifth digit, coarse facies, hirsutism/hypertrichosis, developmental delay and intellectual disability of variable degree and growth impairment. Congenital anomalies may include cardiac, genitourinary and central nervous system malformations whereas congenital diaphragmatic hernia (CDH) is rarely reported. The genes usually involved in CSS pathogenesis are ARID1B (most frequently), SMARCA4, SMARCB1, ARID1A, SMARCE1, DPF2, and PHF6 . Here, we present two cases of CSS presenting with CDH, for whom Whole Exome Sequencing (WES) identified two distinct de novo heterozygous causative variants, one in ARID1B (case 1) and one in SMARCA4 (case 2). Due to the rarity of CDH in CSS, in both cases the occurrence of CDH did not represent a predictive sign of CSS but, on the other hand, prompted genetic testing before (case 1) or independently (case 2) from the clinical hypothesis of CSS. We provide further evidence of the association between CSS and CDH, reviewed previous cases from literature and discuss possible functional links to related conditions.